METHODS OF EXAMINATION OF CHRONIC ETHMOIDITIS - Khodjanov Shokhimardon Khodjanovich; Djuraev Jamolbek Abdukaharovich; Soatov Ilyasjon Olim ogli; Rasulova Nasiba Shavkatovna; Mardonov Khurshed Azamkul ugli (Web of Journals Publishing, 2024)
For the first time, the features of the anatomical structure of the ethmoid bone were determined in patients with ethmoiditis. The relationship between the anatomical structure of the ethmoid bone cells and the volume of the inflammatory process, its localization and severity has been determined. For the first time, the frequency of damage to different groups of cells was determined in isolated ethmoiditis and in combination with damage to other sinuses.
Keywords: Chronic ethmoiditis, sinus surgery, endoscopy, FESS operations